Optimización del sistema de explotación para el área minera “Cabrera Armijos” código 1905510007, sector Quiringue, Parroquia Chicaña, Cantón Yantzaza, Provincia de Zamora Chinchipe. - Preciado Cuenca, Dalembert Alexis (2024)
The present research titled “Optimization of the exploitation system for the Cabrera Armijos mining area code 1905510007, Quiringue sector, Chicaña parish, Yantzaza canton, Zamora Chinchipe province, with an extension of 5 contiguous mining hectares, whose aim is to propose an optimization appropriate to the current extraction system of aggregates and stones materials, this was carried out through the fulfillment of a sequence of objectives which begins with the topographic and geological characterization of the study area, the determination of the quality of the exploitable material, the calculation of existing reserves through the application of the average height method and the definition of the processes or activities necessary to carry out technical, environmental and socially responsible exploitation, for which an ideal exploitation design was developed that will improve the efficiency of the processes through the use of the machinery and infrastructure necessary for each of them. For the implementation of the exploitation system, firstly a multi-criteria analysis was carried out where the comparison of 2 alternative extraction systems was made in relation to their advantages and disadvantages, once the appropriate exploitation system was chosen, activities such as uncovering, preparation and exploitation was considerate, each of these following their application processes and costs. Once the previous activities have been defined, an economic evaluation of the implementation of the extraction system was carried out, which is beneficial for the development of the mining concession. Keywords: reserves, aggregates and stones, exploitation system.